Provinces and Local Government Revenues Structures and Intra-Province Economic Disparity - Riatu M. Qibthiyyah (Economics and Finance in Indonesia, 2017)
One of major policies of Indonesia Decentralisation is the adoption on various type of revenue sharing among provinces and local governments and also the devolved of taxes to lower level government in particular to the province level. Challenges of policy toward higher degree of revenue autonomy, is that an increase in revenue sharing as well as devolved taxes would enhance economic disparity among regions. Further, our finding shows that different types of revenue sharing seem to have different effect on intra-province economic disparity.